The role of gender in English language learning anxiety among tertiary students / Yeo Jiin Yih, Vicky Chin and Ting Hie Ling - Yeo, Jiin Yih; Chin, Vicky; Ting, Hie Ling (2017)
Anxiety is one of the crucial factors that influence second language learning. The feeling of stress, anxiety and worry while engaging in a target language could hamper students’ learning regardless of gender. In relation to this, this study aimed to examine the role of gender in second language learning among tertiary students in Malaysia. Data analysis on the Foreign Language Classroom Anxiety Scale (FLCAS) items were analysed using SPSS 22.Descriptive analysis, Independent Sample T-test and Pearson Correlation were used in the study. The findings revealed that male students were slightly more anxious than female students. The study also indicated thatthere was no significant relationship between gender and language learning anxiety. However, anxiety factors such as fear of negative evaluation and communication speech apprehenstionwere significantly related to gender.